Produktivitas Alat Tangkap Purse Seine yang Beroperasi di Perairan Teluk Ambon Luar, Maluku - Kedswin Gerson Hehanussa; Friesland Tuapetel; Rahmat Hidayat Sanduan (Jurnal Perikanan Unram, 2024)
The decline in fish populations can negatively impact the livelihoods of fishermen and local food security. Therefore, maintaining the sustainability of fisheries is an urgent necessity. Evaluating the productivity of purse seine catches in the outer waters of Ambon Bay is crucial in this context. This study aims to measure the productivity level of purse seine fishing gear and identify the factors that influence it. The research was conducted from June 2023 to May 2024 in Laha Village, Outer Ambon Bay, Ambon Island. The research method used is a quantitative descriptive method, which aims to describe the productivity of purse seine fishing gear in detail based on data obtained in the form of graphs and tables. Data collection was carried out through field surveys and direct observations during fishing activities. The data analysis results showed that the highest volume and number of trips were in November, with 18 trips and a production volume of 644 kg/trip, while the lowest was in May, with 12 trips and a production volume of 184 kg/trip.